Simultaneous bilateral contracture of the infraspinatus muscle - Franch, J.; Bertrán, J.; Remolins, G.; Fontecha, P.; Díaz-Bertrana, M.C.; Durall, I. (Veterinary and Comparative Orthopaedics and Traumatology, 2009)
A case of bilateral fibrotic contracture of the infraspinatus muscles in a five-year-old Belgian Shepherd dog is described. The dog was presented with progressive forelimb lameness with postural and gait abnormalities three months after an episode of overexertion. When walking, the lower part of both forelimbs swung in a lateral arc causing a circumduction movement and in the standing position, the dog showed elbow adduction with external rotation of the distal part of both front limbs. Orthopaedic examination revealed bilateral atrophy of both infraspinatus and supraspinatus muscles and restriction in the range of motion of both shoulders, especially when attempting abduction and flexion. No specific findings were observed in the shoulder or elbow radiographs but hyper-echogenic areas were evident in the ultra-sonographic examination of both infraspinatus muscles. A diagnosis of fibrotic contracture of both infraspinatus muscles was established and bilateral tenectomy of the insertion tendons of the infraspinatus muscles was performed. Complete recovery of the animal was achieved after the surgery, which was confirmed in a long-term follow-up (10 months). In conclusion, physical examination and ultra-sonography allowed a proper diagnosis of the condition, and tenectomy of the infraspinatus muscles resulted in a complete recovery of the patient even with bilateral involvement.
Keywords: Infraspinatus muscle; contracture; bilateral involvement; dog; tenectomy